2010
DOI: 10.1007/s11999-010-1298-4
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Fluid Biomarkers for Periprosthetic Infection

Abstract: Background We have previously described a unique gene expression signature exhibited by synovial fluid leukocytes in response to bacterial infection, identifying a number of potential biomarkers for infection. However, the diagnostic performance of these potential biomarkers in an immunoassay format is unknown.Questions/purposes We therefore evaluated the sensitivity, specificity, and accuracy of several potential synovial fluid biomarkers for infection, and compared them to current standards of testing for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(118 citation statements)
references
References 16 publications
2
106
0
10
Order By: Relevance
“…(3) What is the accuracy of synovial fluid cytokines and the Musculoskeletal Infection Society (MSIS) criteria to rule out PJI after first-stage explantation? (4) What are the most studied synovial fluid cytokines for diagnosing PJI as reported in the literature and what are their cumulative diagnostic accuracy? Methods Between May 2013 and March 2014, 104 patients with painful THA and TKA evaluated for possible PJI were included in our study.…”
Section: Introductionmentioning
confidence: 99%
“…(3) What is the accuracy of synovial fluid cytokines and the Musculoskeletal Infection Society (MSIS) criteria to rule out PJI after first-stage explantation? (4) What are the most studied synovial fluid cytokines for diagnosing PJI as reported in the literature and what are their cumulative diagnostic accuracy? Methods Between May 2013 and March 2014, 104 patients with painful THA and TKA evaluated for possible PJI were included in our study.…”
Section: Introductionmentioning
confidence: 99%
“…Synovial biomarkers may provide such a test. A preliminary study showed that the AD-1 assay can quantitatively detect the level of the AD-1 biomarker in synovial fluid and may prove to be highly sensitive and specific for diagnosis of PJIs [2]. However no independent study has confirmed the use of the AD-1 assay in diagnosing a PJI.…”
Section: Discussionmentioning
confidence: 99%
“…Synovial fluid biomarkers such as cytokines, inflammatory proteins, and antimicrobial peptides may provide such a tool, but the best biomarker or combination of biomarkers has yet to be determined [2]. One biomarker, the alpha defensin-1 (AD-1) protein has shown promise [7].…”
Section: Introductionmentioning
confidence: 99%
“…We recognize there are numerous other tests currently being evaluated, including measurement of CRP from the synovial fluid [12], synovial leukocyte esterase [13], sonication of explanted prosthetics [17], and molecular techniques such as PCR [10] and other molecular markers such as IL-6 [2,4,6]. As these or other techniques become validated and widely available, the currently proposed definition may require modification.…”
Section: Future Developmentsmentioning
confidence: 99%